2021
DOI: 10.48550/arxiv.2111.01417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinguishing between $Λ$CDM and $f(R)$ gravity models using halo ellipticity correlations in simulations

Abstract: There is a growing interest of utilizing intrinsic alignment (IA) of galaxy shapes as a geometric and dynamical probe of cosmology. In this paper we present the first measurements of IA in a modified gravity model using the gravitational shear-intrinsic ellipticity correlation (GI) and intrinsic ellipticity-ellipticity correlation (II) functions of dark-matter halos from 𝑓 (𝑅) gravity simulations. By comparing them with the same statistics measured in ΛCDM simulations, we find that the IA statistics in diffe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…It should be worth discussing why we utilized the massive group/cluster halos rather than the galactic counterparts as the main targets for these new diagnostics. In the original work of Chuang et al (2021) who for the first time suggested the halo intrinsic shape alignments as a test of f (R) gravity, their analysis was made exclusively on the galactic scale under the assumption that the intrinsic shape alignments of galactic halos are observable quantities since the shape orientations of the DM components of galactic halos should be well aligned with those of their observable stellar components. However, a recent numerical analysis based on high-resolution hydrodynamical simulations revealed that this assumption cannot be justified on the galactic scale, witnessing significant misalignments between the shape orientations of the DM and stellar components of the galactic halos (Lee & Moon 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be worth discussing why we utilized the massive group/cluster halos rather than the galactic counterparts as the main targets for these new diagnostics. In the original work of Chuang et al (2021) who for the first time suggested the halo intrinsic shape alignments as a test of f (R) gravity, their analysis was made exclusively on the galactic scale under the assumption that the intrinsic shape alignments of galactic halos are observable quantities since the shape orientations of the DM components of galactic halos should be well aligned with those of their observable stellar components. However, a recent numerical analysis based on high-resolution hydrodynamical simulations revealed that this assumption cannot be justified on the galactic scale, witnessing significant misalignments between the shape orientations of the DM and stellar components of the galactic halos (Lee & Moon 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Chuang et al (2021) suggested that the intrinsic shape alignment of galactic halos be useful as a probe of gravity, showing by N-body simulations that its strength significantly differ between the ΛCDM and a f (R) gravity model with f R0 = 10 −5 (fR5). Here, the intrinsic shape alignment of galactic halos refers to the phenomenon that the shape orientations of galactic halos exhibit a tendency of being preferentially aligned with the hosting filaments, which is believed to originate from the occurrence of anisotropic merging along the filamentary cosmic web (Altay et al 2006;Hahn et al 2007;Zhang, Yang & Faltenbacher 2009;Zhang et al 2013;Chen et al 2016;Lee 2019, and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Yu et al (2020) claimed that the intrinsic spin alignments of galaxies could be used to examine the violation of chiral symmetry of weak interactions in the early universe. Taruya & Okumura (2020) suggested that the two-point correlations of halo intrinsic alignments should be a sensitive tracer of the cosmic growth history (see also Chuang et al 2021). found that the dark energy (DE) equation of state can in principle be constrained by the mass scales at which the preferential alignments of DM halo spins with the tidal principal axes exhibit transitions.…”
Section: Introductionmentioning
confidence: 99%